The Influence of the Construction of the Ocarina – Bengkong Bridge on Economic Aspects and Social Aspects In Bengkong District, Batam City - Ginting, Herman Suranta; Sidabutar, Yuanita FD (Borong Newinera Publisher, 2024)
Infrastructure development has the potential to have an important influence on various aspects of regional development. One important piece of infrastructure is a bridge. This study aims to analyze the influence of the construction of the Ocarina - Bengkong Bridge on economic and social aspects in Bengkong sub-district. This research uses quantitative methods by distributing questionnaires to the community around the Bengkong bridge. In the economic aspect, the research results show that the construction of the bridge has made a positive contribution to economic growth in Bengkong sub-district. The availability of better accessibility between Ocarina and Bengkong has increased population mobility, enabled the growth of the trade sector, and supported the development of the tourism sector in the region. Apart from that, the construction of the bridge also triggers an increase in property values and investment around the area. In the social aspect, bridge construction has brought positive changes in people's lives. Better mobility increases social connectivity between regions, facilitates cultural exchange, and strengthens community integration. Apart from that, increasing accessibility also increases people's access to education and health services. However, this study also identified several challenges and negative influences, such as increased traffic flow which can cause congestion and environmental impacts that need to be managed well and wisely. This research provides important insights for policy makers, related parties and the general public about the importance of infrastructure such as bridges in improving the economic and social welfare of a region.